2021
DOI: 10.1017/s1463423621000177
|View full text |Cite
|
Sign up to set email alerts
|

A focus group study of older Chinese people with CVD patients in the North West of the UK

Abstract: Background: Cardiovascular disease (CVD) is the leading cause of death for Chinese migrants around the world. Chinese CVD patients rely heavily on their native Chinese language, cultural values and beliefs, which adds challenges for the healthcare providers to offer primary healthcare services with standard protocol. The inappropriate treatment could lead to life loss, mistrust in doctor-patient relationship and heavy burden for healthcare funding. Methods: 28 participants were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Of the total 86 studies identified from the electronic database searches, 27 studies used quantitative methods via survey, 50 employed qualitative methods and nine employed mixed methods combining surveys and interviews. Of the 50 qualitative studies, 37 (74%) used a single method of qualitative data-collection: individual interviews ( n = 26) [ 14 39 ], focus-group discussions (FGD) ( n = 10) [ 40 49 ] or group interview ( n = 1) [ 50 ]. Thirteen of the 50 qualitative studies used two or more methods for data collection [ 51 63 ] combining individual interviews with FGDs ( n = 9) [ 52 , 53 , 55 – 59 , 63 ], with participant observation ( n = 3) [ 54 , 60 , 62 ], with group interviews ( n = 1) [ 61 ] or with FGDs and a site visit ( n = 1) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the total 86 studies identified from the electronic database searches, 27 studies used quantitative methods via survey, 50 employed qualitative methods and nine employed mixed methods combining surveys and interviews. Of the 50 qualitative studies, 37 (74%) used a single method of qualitative data-collection: individual interviews ( n = 26) [ 14 39 ], focus-group discussions (FGD) ( n = 10) [ 40 49 ] or group interview ( n = 1) [ 50 ]. Thirteen of the 50 qualitative studies used two or more methods for data collection [ 51 63 ] combining individual interviews with FGDs ( n = 9) [ 52 , 53 , 55 – 59 , 63 ], with participant observation ( n = 3) [ 54 , 60 , 62 ], with group interviews ( n = 1) [ 61 ] or with FGDs and a site visit ( n = 1) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bicultural workers supported data collection ( n = 24) [ 14 , 15 , 20 , 21 , 24 , 25 , 31 , 33 , 34 , 37 , 42 44 , 46 48 , 50 53 , 56 , 58 , 61 , 63 ] and data analysis ( n = 12) [ 14 , 15 , 24 , 31 , 33 , 43 , 44 , 47 , 52 , 53 , 55 , 56 ]. Most (86%; 43/50) of the qualitative studies conducted data collection in the respondents’ preferred community language via bicultural workers or interpreters [ 14 , 15 , 17 22 , 24 35 , 37 39 , 41 50 , 53 56 , 58 63 ]. In addition to supporting language and cultural needs, the need for flexible and supportive data collection processes to enable ethnically diverse communities to engage in PREMs was reported in several studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Chinese people hence adopt the belief that TCM and Western medicine are complementary in a specific way; the body and health are also sometimes conceptualised through terms of traditional medicine (Liu et al, 2015;Wood, 2016). However, as TCM is not part of the health-care system in Western countries, some older Chinese migrants have turned to selfmedication or private TCM practitioners for additional treatments while receiving treatments of Western medicine (Pang et al, 2003;Wu et al, 2007;Wood, 2016;Speed et al, 2021).…”
Section: Synthesismentioning
confidence: 99%
“…Ethnic Chinese is one of the largest Asian sub-groups in the UK and the population has doubled in the last 10 years (GOV.UK 2020). They have specific spiritual and cultural beliefs which may impact their overall health (Speed et al 2021;Niu et al 2020). This study explored how ethnic Chinese residing in England perceive spirituality and spiritual care to help nurses respond to their cultural and religious needs.…”
Section: Introductionmentioning
confidence: 99%